PENGARUH KEPUASAN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI KANTOR SEKERTARIAT KOTA MAKASSAR - Ahmad Musseng (AkMen JURNAL ILMIAH, 2013)
This research is aimed to analyze the influence of work satisfaction, and oganizational culture toward the employees’ performance at Office of the Secretariat of Makassar City and to find out the dominant factors that mostly influence the performance of the employees. The respondents of this research are te employees of Office of the Secretariat of Makassar City. The samples are taken by using Slovin Formula. There were 77 samples selected from 328 populations. The data analysis was carried out with multiple regression analysis. The result show that work satisfaction, and oganizational culture toward the employesss performance. The most dominant factor which influences the employees performance work satisfaction.